Adnexal polyp of the skin. Report of two cases. - Gualandri, L.; Boccardi, D.; Betti, R.; Menni, S. (European Journal of Pediatric Dermatology, 2003)
We describe two newborns showing small skin-colored pedunculated papules localized on the areola of the nipple. The clinical and hystological features were compatible with the diagnosis of adnexal polyp. Adnexal polyp is a small congenital tumor of the skin occurring most frequently on the areola of the nipple of the neonate.